Canada: Peary Arctic Club, 1898-1902, bringing out the Greely records - Peary, Robert E. (Robert Edwin), 1856-1920 (1898)
Bringing out the Greely records http://www.matthewhenson.com/1909NPtrip/1910b.html; Ft Conger headquarters of Greely Expedition